Takotsubo cardiomyopathy in peripartum period: a case report - Sundararajan, Chitramani; Naveena, Thamizh; Kubendiran, Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Cardiomyopathy is a group of disorders characterised by structural and functional abnormalities in the myocardium in the absence of other cardiac diseases of myocardial abnormality. Its occurrence in pregnancy is uncommon and exact incidence is unknown even though some studies shows that the incidence of peripartum cardiomyopathy is 1 in 1000 to 4000 births. Here we have discussed about a 34 years primigravida with twin pregnancy conceived after 12 years of married life by assisted reproductive technique (ART), admitted with preterm premature rupture of membranes (PPROM) at 28 weeks of gestation who developed a rare condition called Takotsubo cardiomyopathy (TC) in the peripartum period. She was managed in intensive care unit with oxygen supplementation, beta blockers, diuretics and heparin. Patient had an excellent recovery in the early postoperative period.